How Macbeth Washes Her Hands. Diderot’s Conception of Movement, between His First Writings on Theatre Aesthetics and the Salons (Itinera, 2021)
In the pages of Diderot, theatre is able to enclose a precise sense of movement. By distancing itself from conventions, poses, mannerisms, and affectations, the stage gesture can embody a fundamental dynamism and vitalism. Such a gesture should be read in the light of Diderot’s materialistic conception of nature. The centrality of body language and of pantomime is a leitmotiv of the art of the French eighteenth-century actor. However, in Diderot’s formulation of a dramaturgy of space and motion, as well as in the theorization of the aesthetic relationship between actor and spectator, we find a peculiar synthesis of the dichotomies illusion / fiction and sensitivity / detachment, which emerge with regard to the fictional status of theatre in the Enlightenment environment. In this sense, the analogy with the pictorial sphere turns out to be a fundamental resource. There is a sort of circular reasoning that induces in Diderot the desire of reforming theatre on the basis of painting: a painting which is however conceived in a radically dramatic way. Concepts such as absorption, theatricalization, decisive moment, unity of action, and fourth wall are applied to theatre as well as to painting. Therefore, they can be included within a more general interpretation of the sense of movement, according to the principles of fluidity, harmony, and transformation that regulate both nature and the work of art.
Keywords: Theater, Body, Aesthetic experience, Fiction, Actor, Diderot.